Quorum Sensing, A Communication of Bacteria: Control Mechanism of Pathogenesis in Pseudomanas aeruginosa - เลิศวรปรีชา, มณฑล; สุวรรณมณี, ญฏารัตน์ (KKU Science Journal, 2014)
Controlling the work of human and animal cells are associated with cell to cell communication. The mechanism can be divided into two types, first is direct cell to cell contact and second is mediate by mediator molecules which release and bind on to the cell surface molecules, and activate cell functions via signaling pathway. Similarly to mammalian cells, bacterial cells also have a communication system which named as a “quorum sensing system”. Each different bacterial species are able to produce different molecules called autoinducer, which act as a mediator to communication. This quorum sensing system plays an important role for bacteria in respond to environmental condition and control expression of several virulence genes. In this review, the basic knowledge and mechanism of the quorum sensing and the role of quorum sensing which involved to virulence genes expression in P. aeruginosa will be discussed.